Muhajirin Amsar Contribution on Legal Hadîts Interpretation - Masykuri Hakim (AHKAM : Jurnal Ilmu Syariah, 2015)
Muhajirin Amsar is a native Betawi scholars.  Muhajirin Amsar explained hadîts by ignoring other scholars opinion in terms of grammar, so that the reader can immediately understand the content of the hadîts. He also did not provide his own opinion after the scholars opinion, it seems he more likely put the reader to choose freely due to the problem  as the issue of khilâfiyyah.DOI: 10.15408/ajis.v15i1.2849